Causalism versus Propensionism in the Philosophy of Biology: A Case of Philosophical Underdetermination? - CERNEA, MIHAIL-VALENTIN (Filozofia, 2024)
This paper has two objectives: (1) to define philosophical underdetermination in contrast with the usual empirical underdetermination that has been invoked by so many philosophers of science, expanding on recent work in ethics regarding moral underdetermination; (2) to prove that the debate between the causalist and propensionist interpretations of causation in the structure of evolutionary theory is better understood when we consider the two positions philosophically underdetermined. This means that we cannot decide between the two interpretations of the notion of cause implied by natural selection by appealing to scientific practice. If philosophical interpretations of science are underdetermined in the way outlined in this paper, then the only way to move the debate forward is through more thorough philosophical work and theoretical refinements.